Dynamic soil–structure interaction of a three-span railway bridge subject to high-speed train passage - Tehrani, Seyed Amin Hosseini; Andersson, Andreas; Zanganeh, Abbas; Battini, Jean-Marc (Engineering structures, 2024)
In this study, the influence of Soil-Structure Interaction (SSI) on the dynamic behavior of a three-span concrete slab railway bridge with integrated retaining walls is investigated. The bridge is subjected to controlled excitations using a hydraulic actuator with different frequencies and load amplitudes. A 3D model of the railway bridge-soil system is implemented and calibrated using the experimental frequency response functions at each sensor location. A soil-free model is also created to compare with the calibrated model. It is observed that the dynamic behavior of the railway bridge is substantially altered by the presence of the surrounding soils, and neglecting SSI can lead to underestimation and inaccurate results. Additionally, the calibrated model is used for further train-passage analyses. For the studied bridge, neglecting SSI increases the maximum acceleration response of the bridge during high-speed train passages from 5.5 m/s2 up to 14.5 m/s2. It is also shown that the response of the bridge during train passage is predominantly influenced by its first bending mode, with higher modes inducing no discernible effect. Finally, parametric studies are performed in order to study the uncertainties related to the soil properties.